A Phase 1/2 Randomized Study to Evaluate the Safety, Tolerability, and Immunogenicity of Nucleoside-Modified Messenger RNA Influenza Vaccines in Healthy Adults - Angela Branche; Mark J. Mulligan; Alok Maniar; Orlando Puente; Islamiat Oladipupo; Graham Crowther; Agnieszka M. Zareba; Zhuobiao Yi; Ingrid Scully; Emily Gomme; Kenneth Koury; Nicholas Kitchin; et al. (Vaccines)
Background/Objectives: Circulating influenza strains antigenically differing from vaccine antigens increase disease burden by decreasing vaccine efficacy. Nucleoside-modified mRNA (modRNA) influenza vaccines may facilitate rapid production allowing later antigen selection and improved antigenic similarity compared to circulating strains. We studied different influenza modRNA vaccine (IRV) formulations and dose levels. Methods: This phase 1/2 randomized study evaluated IRV safety/tolerability and immunogenicity in healthy 18- through 85-year-olds. Based on safety and immunogenicity for different IRV doses, schedules, and valencies versus the quadrivalent influenza vaccine (QIV; Fluzone High-Dose Quadrivalent, Sanofi Pasteur) in phase 1 (65–85-year-olds), quadrivalent IRV (qIRV) was further evaluated in 65- through 85-year-olds and 18- through 64-year-olds in phase 2, leading to phase 3 dose selection. Results: Phase 1 (65–85-year-olds) safety/tolerability and immunogenicity findings supported qIRV 30-µg and 60-µg phase 2 assessment (18–85-year-olds, N = 610). qIRV was well tolerated. Injection site pain was the most frequently reported local reaction. Reactogenicity event incidences ≤ 7 days postvaccination for qIRV were generally higher versus QIV, observed more frequently in 18- through 64-year-olds than 65- through 85-year-olds, and showed dose-related trends (60 μg > 30 μg). qIRV and QIV adverse event profiles in 65- through 85-year-olds were similar. There were higher postvaccination hemagglutination inhibition assay geometric mean titers and fold rises and seroconversion rates observed with qIRV versus QIV for A strains, with no consistent pattern for B strains. Cell-mediated immune responses to qIRV by Day 7 showed overall higher T-cell responses against all strains versus QIV. Antibody and cell-mediated immune responses showed comparable trends across qIRV doses in 18- through 85-year-olds; a dose-related pattern was observed in 65- through 85-year-olds (60 μg > 30 μg). Conclusions: Phase 3 investigations of qIRV 60 µg in older adults and qIRV 30 µg in younger adults are warranted (ClinicalTrials.gov Identifier: NCT05052697).